EFFECT OF EMBLICA OFFICINALIS (AMLA) ON APOPTOTIC CELL DEATH FOLLOWING ISCHEMIA REPERFUSION INJURY IN RATS - DINESH TRIPATHI; ARTI VERMA; SANDEEP BHATTACHARYA; SUNITA TIWARI (International Journal of Pharma and Bio Sciences, 2015)
Cell death following ischemia reperfusion injury leads to life threatning problems in patients suffering from cerebral stroke. The aim of this study was to investigate the neuroprotective effects of Emblica Officinlis (amla) fruit extract on neuronal apoptosis following cerebral ischemia reperfusion injury.1 hour ischemia followed by 24 hours reperfusion, rats were orally administered amla fruit extract. Apoptotic cells in brain were determined by performing flow cytometry. The results showed that amla extract significantly decreased the apoptotic cells by flow cytometry 24 hours after the ischemic injury compared with the MCAO group. This study suggests that amla may be used for treatment of ischemic stroke as a neuroprotective agent.